A high niobium stainless steel flux-cored welding wire and preparation method thereof
By adding fluoride, reducing metal elements, and increasing the content of gold red stone powder and silicon powder to the core powder of 347 stainless steel core gas warranty, it solves the problem of increasing the lack of residue after the NB element content is improved in the welding wire. It realizes the good residue performance and high temperature corrosiveness of the weld.
Patent Information
- Application Number
- CN202411457832.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-18
AI Technical Summary
After increasing the Nb element content in the 347 stainless steel flux-core gas-protected welding wire, the desorption performance of the welding wire clad metal becomes worse, and pore defects are easily generated.
By adding fluoride such as LAF3 and CEF3 to the drug core powder, and include reduction metal elements such as AL, Mg, and increasing the content of gold red stone powder and silicon powder Residual deserture performance.
Improve the residue performance of the welding wire, reduce the content of the spine -stones of NB in the weld melting metal, reduce the occurrence of pore defects, and enhance the high temperature corrosiveness of the weld.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flux-cored welding wires, and in particular to a high-niobium stainless steel flux-cored welding wire and a preparation method thereof. Background Art
[0002] 347 stainless steel flux-cored gas-shielded welding wire contains Nb element in its welding wire composition. When 347 stainless steel flux-cored gas-shielded welding wire is used for welding high-temperature pressure vessels used in nuclear power equipment, the niobium in the welding wire cladding metal has a very low capture cross-section for thermal neutrons. At the same time, Nb and C have a high affinity, and the two are easily combined to form Nb carbides, thereby reducing the C content in the weld and preventing C from combining with the chromium element in the weld to form chromium carbide. Accordingly, it is not easy to form a chromium-depleted zone at the grain boundary of austenite, thereby significantly improving the corrosion resistance of stainless steel.
[0003] At present, the Nb content in the weld metal of 347 stainless steel gas-shielded flux-cored welding wire after welding is generally 0.3%-0.4%. Studies have shown that when the Nb content in the weld metal is increased to more than 0.8%, the weld can obtain better high-temperature corrosion resistance and lower crack sensitivity. However, after increasing the niobium content in 347 stainless steel gas-shielded flux-cored welding wire, the slag removal performance of the slag on the surface of the weld metal will deteriorate, and niobium is more likely to form a niobium spinel oxide. This niobium spinel oxide has a strong bonding force with the surface of the weld metal, resulting in poor slag removal performance of the weld metal and easy slag sticking. In addition, after simply increasing the Nb content in 347 stainless steel gas-shielded flux-cored welding wire, the obtained wire is very likely to produce porosity defects in the weld metal when the mixed shielding gas welding is carried out. Summary of the invention
[0004] The technical problem in the prior art is that, based on the original composition of 347 stainless steel flux-cored gas shielded welding wire, increasing the Nb content in the welding wire composition will deteriorate the slag removal performance of the welding wire cladding metal. In view of the above problem, the present invention provides a high-niobium stainless steel flux-cored welding wire, comprising an iron sheet and a flux core powder, the thickness of the iron sheet is 0.4 mm, the flux core powder uniformly fills and fills the cylindrical cavity formed by the iron sheet, the filling rate of the flux core powder is 22-28%, and the iron sheet is a 304L stainless steel strip;
[0005] The drug core powder comprises the following components in terms of weight percentage:
[0006] Niobium iron alloy powder 7-12%;
[0007] Rutile powder 20-30%;
[0008] Alumina powder 2-4%;
[0009] Iron oxide powder 1-5%;
[0010] Fluoride powder 3-4%;
[0011] Silicon dioxide powder 2-3%;
[0012] Titanium-iron alloy powder 1-3%
[0013] Zirconium iron alloy powder 1-2%
[0014] Bismuth oxide powder 0.2-0.35%
[0015] Manganese powder 4-6%;
[0016] Arc stabilizer 4-5%
[0017] Nickel powder 10-12%;
[0018] Chromium powder 16-19%;
[0019] Magnesium powder 0-1.5%
[0020] Aluminum-iron alloy powder 0-2%
[0021] Iron powder residue;
[0022] The weight ratio of the rutile powder to the silicon dioxide powder is 10:1.
[0023] The mass ratio of niobium to iron in the ferroniobium alloy powder is 7:3;
[0024] The iron oxide powder includes at least one of ferric oxide and ferroferric oxide;
[0025] The fluoride powder is a mixture of cryolite and lanthanide rare earth fluoride;
[0026] The mass ratio of titanium to iron in the titanium-iron alloy powder is 3:7;
[0027] The zirconium element zirconium accounts for more than 98% of the zirconium-iron alloy powder;
[0028] The arc stabilizer includes at least one of titanium oxide, magnesium oxide and potassium oxide;
[0029] The mass ratio of aluminum element to iron element in the aluminum-iron alloy powder is 1:1.
[0030] Preferably, the fluoride powder is a mixture of cryolite and lanthanide rare earth fluoride in a mass ratio of 3:1.
[0031] Preferably, the lanthanide rare earth fluoride includes at least one of LaF3 and CeF3.
[0032] Preferably, the iron oxide powder is a mixture of ferric oxide and ferrous oxide in a mass ratio of 1:2.
[0033] Preferably, the purity of manganese powder, nickel powder, chromium powder, iron powder and magnesium powder is greater than 99.9%.
[0034] Preferably, the average particle size of the drug core powder is 300-500 mesh.
[0035] Preferably, the added weight percentage of the magnesium powder is 1-1.5%.
[0036] Preferably, the added weight percentage of the aluminum-iron alloy powder is 1-2%.
[0037] Preferably, the preparation method of the high niobium stainless steel flux-cored welding wire comprises the following steps:
[0038] (1) Roll the 304L stainless steel strip into a U-shape and add the formulated amount of core powder into the U-shaped groove;
[0039] (2) The U-shaped groove is rolled into an O-shaped steel pipe, and then rolled, bright annealed, drawn and reduced, and mechanically cleaned to obtain a Φ1.2-1.6mm high niobium stainless steel flux-cored welding wire.
[0040] The present invention has the following beneficial effects:
[0041] (1) After the cladding welding is completed, the Nb content in the weld cladding metal formed by the high-niobium stainless steel welding wire obtained by the present invention reaches more than 0.8%, which can effectively ensure the high-temperature corrosion resistance of the high-temperature pressure vessel;
[0042] (2) Directly increasing the content of Nb element in 347 stainless steel flux-cored gas shielded welding wire on the basis of its original composition content, the slag removal performance of the obtained weld cladding metal is poor, and the obtained weld cladding metal is prone to pores. In order to solve the above problems, the present invention has found that simply increasing the Nb element in the composition of 347 stainless steel flux-cored gas shielded welding wire can easily form more Nb spinel oxides (belonging to the welding slag component) during the welding process. The linear expansion coefficient between the Nb spinel oxide and the metal film on the weld surface (Fe oxide film) is relatively small. Both the Fe oxide and the Nb spinel oxide are body-centered cubic structures, and the bonding force between the two is relatively strong, resulting in poor slag removal performance of the weld cladding metal.
[0043] In view of the above problems, the present invention adds fluoride, such as LaF3 and CeF3, to the flux core powder component, which can perform allotropic transformation on the spinel oxide of Nb formed in the welding slag through metallurgical reaction during the welding process, thereby reducing the content of the spinel oxide of Nb in the slag, and also helps to reduce the bonding strength between the spinel oxide of Nb and the metal film on the surface of the weld, thereby improving the slag removal property of the welding wire;
[0044] The flux core powder of the present invention also contains reducing metal elements, such as Al, Mg and other elements, which can reduce the oxide film formed on the surface of the weld during welding. First, it can assist in deoxidation and reduce the oxygen content in the weld to achieve the purpose of reducing pores; second, when reducing the oxide film, part of the oxides that are not conducive to slag removal (such as spinel oxides of Nb) can be reduced, thereby improving the slag removal performance of the weld.
[0045] The present invention also increases the content of rutile powder (TiO2) and silicon dioxide powder in the welding wire core component and reasonably controls the ratio of the added amounts of the two, so that the Nb element in the slag preferentially combines with titanium oxide during the welding process to form a metal oxide that is easy to fall off from the weld metal surface, thereby achieving the purpose of improving the slag removal performance of the weld cladding metal. The possible reasons are as follows:
[0046] During the welding process, SiO2 and Mn are deoxidized together to achieve the effect of reducing the oxygen content in the weld, thereby reducing the spinel oxide content of Nb in the slag. The rutile powder forms a large amount of titanate mixture in the slag, mainly including FeTiO5 and CrTiO2, etc. These titanates have a tight structure and will form different tissues according to the Ti content. The present invention adjusts the formula of the core component to form a coarse and uneven titanate tissue structure in the slag as much as possible. The coarse and uneven titanate tissue structure will produce greater restraint during solidification, which is conducive to the slag shedding. The coarse and uneven titanate tissue structure also increases the opportunity for TiO2 to combine with the Nb element to form nuclei, thereby reducing the spinel oxide content of Nb in the slag, and finally improving the slag removal property of the slag.
[0047] (3) By rationally designing the formula of the flux-cored welding wire, the high-niobium stainless steel flux-cored welding wire obtained by the present invention has all-position welding capability. DETAILED DESCRIPTION
[0048] The present invention is described in detail below with reference to the examples. However, it should be understood that the following examples are only illustrative of the embodiments of the present invention, and are not intended to limit the scope of the present invention.
[0049] The mass ratio of niobium to iron in the ferro-niobium alloy powder used in the following embodiments of the present invention is 7:3.
[0050] The mass ratio of titanium to iron in the titanium-iron alloy powder used in the following examples of the present invention is 3:7.
[0051] The mass percentage of zirconium element in the ferro-zirconium alloy powder used in the following examples of the present invention is 98%, and the balance is iron.
[0052] The arc stabilizer used in the following embodiments of the present invention is composed of TiO2, K2O, and MgO in a mass ratio of 7:2:1.
[0053] The aluminum-iron alloy powder used in the following embodiments of the present invention has a mass ratio of aluminum to iron of 1:1.
[0054] The purity of manganese powder, nickel powder, chromium powder, iron powder and magnesium powder in the following examples of the present invention is 99.9%.
[0055] Example 1
[0056] A high niobium stainless steel flux-cored welding wire, with a diameter of Φ=1.2, composed of iron sheet and flux core powder, the thickness of the iron sheet is 0.4mm, the flux core powder is evenly filled and fills the cylindrical cavity formed by the iron sheet, the filling rate of the flux core powder is 22%, and the iron sheet is 304L stainless steel strip;
[0057] The drug core powder, in terms of weight percentage, has the following components:
[0058] Niobium iron alloy powder 12%;
[0059] Rutile powder 20%;
[0060] Alumina powder 3%;
[0061] Iron oxide powder 2%;
[0062] Fluoride powder 3%;
[0063] Silicon dioxide powder 2%;
[0064] Titanium Ferroalloy Powder 2%
[0065] Zirconium iron alloy powder 2%
[0066] Bismuth oxide powder 0.3%
[0067] Manganese powder 6%;
[0068] Arc stabilizer 5%
[0069] Nickel powder 12%;
[0070] Chromium powder 16%;
[0071] Magnesium powder 1%;
[0072] Aluminum-iron alloy powder 2%;
[0073] Iron powder residue;
[0074] The fluoride powder is a mixture of cryolite and CeF3 in a mass ratio of 3:1.
[0075] The iron oxide powder is a mixture of ferric oxide and ferrous oxide in a mass ratio of 1:2.
[0076] A high niobium stainless steel flux-cored welding wire, the preparation method thereof has the following steps:
[0077] (1) Roll a 304L stainless steel strip into a U-shape, add a formulated amount of core powder into the U-shaped groove, and the average particle size of the core powder is 300 mesh;
[0078] (2) The U-shaped groove is rolled into an O-shaped steel tube, and the filling rate of the core powder in the O-shaped steel tube is 22%;
[0079] (3) The O-shaped steel pipe is rolled by 6 groups of 30 roller dies, drawn by 1 sizing die, and made into Φ2.0mm stainless steel flux-cored welding wire by wire annealing machine;
[0080] (4) The welding wire obtained in step (3) is then subjected to 10 drawing processes to be made into a Φ1.2 stainless steel flux-cored welding wire.
[0081] Example 2
[0082] A high niobium stainless steel flux-cored welding wire, with a diameter of Φ=1.2, composed of iron sheet and flux-cored powder, the thickness of the iron sheet is 0.4 mm, the flux-cored powder is evenly filled and fills the cylindrical cavity formed by the iron sheet, the filling rate of the flux-cored powder is 23%, and the iron sheet is a 304L stainless steel strip;
[0083] The drug core powder, in terms of weight percentage, has the following components:
[0084] Niobium iron alloy powder 10%;
[0085] Rutile powder 25%;
[0086] Alumina powder 4%;
[0087] Iron oxide powder 5%;
[0088] Fluoride powder 4%;
[0089] Silicon dioxide powder 2.5%;
[0090] Titanium Ferroalloy Powder 3%
[0091] Zirconium iron alloy powder 2%
[0092] Bismuth oxide powder 0.2%
[0093] Manganese powder 5%;
[0094] Arc stabilizer 4%
[0095] Nickel powder 10%;
[0096] Chromium powder 18%;
[0097] Magnesium powder 1.5%;
[0098] Aluminum-iron alloy powder 1.5%;
[0099] Iron powder residue;
[0100] The fluoride powder is a mixture of cryolite and LaF3 in a mass ratio of 3:1.
[0101] The iron oxide powder is a mixture of ferric oxide and ferrous oxide in a mass ratio of 1:2.
[0102] A high niobium stainless steel flux-cored welding wire, the preparation method thereof has the following steps:
[0103] (1) Roll a 304L stainless steel strip into a U-shape, add a formulated amount of core powder into the U-shaped groove, and the average particle size of the core powder is 500 mesh;
[0104] (2) The U-shaped groove is rolled into an O-shaped steel tube, and the filling rate of the core powder in the O-shaped steel tube is 23%;
[0105] (3) The O-shaped steel pipe is rolled by 6 groups of 30 roller dies, drawn by 1 sizing die, and made into Φ2.0mm stainless steel flux-cored welding wire by wire annealing machine;
[0106] (4) The welding wire obtained in step (3) is further subjected to 10 drawing processes to be made into a Φ1.2 stainless steel flux-cored welding wire.
[0107] Example 3
[0108] A high niobium stainless steel flux-cored welding wire, with a diameter of Φ=1.2, composed of iron sheet and flux-cored powder, the thickness of the iron sheet is 0.4 mm, the flux-cored powder is evenly filled and fills the cylindrical cavity formed by the iron sheet, the filling rate of the flux-cored powder is 25%, and the iron sheet is a 304L stainless steel strip;
[0109] The drug core powder, in terms of weight percentage, has the following components:
[0110] Niobium iron alloy powder 9%;
[0111] Rutile powder 27%;
[0112] Alumina powder 3%;
[0113] Iron oxide powder 1%;
[0114] Fluoride powder 3%;
[0115] Silicon dioxide powder 2.7%;
[0116] Titanium Ferroalloy Powder 1%
[0117] Zirconium iron alloy powder 1%
[0118] Bismuth oxide powder 0.3%
[0119] Manganese powder 4.5%;
[0120] Arc stabilizer 4.5%
[0121] Nickel powder 11%;
[0122] Chromium powder 19%;
[0123] Magnesium powder 1%;
[0124] Aluminum-iron alloy powder 2%;
[0125] Iron powder residue;
[0126] The fluoride powder is a mixture of cryolite and LaF3 in a mass ratio of 3:1.
[0127] The iron oxide powder is a mixture of ferric oxide and ferrous oxide in a mass ratio of 1:2.
[0128] A high niobium stainless steel flux-cored welding wire, the preparation method thereof has the following steps:
[0129] (1) Roll a 304L stainless steel strip into a U-shape, add a formulated amount of core powder into the U-shaped groove, and the average particle size of the core powder is 400 mesh;
[0130] (2) The U-shaped groove is rolled into an O-shaped steel tube, and the filling rate of the core powder in the O-shaped steel tube is 25%;
[0131] (3) The O-shaped steel pipe is rolled by 6 groups of 30 roller dies, drawn by 1 sizing die, and made into Φ2.0mm stainless steel flux-cored welding wire by wire annealing machine;
[0132] (4) The welding wire obtained in step (3) is further subjected to 10 drawing processes to be made into a Φ1.2 stainless steel flux-cored welding wire.
[0133] Example 4
[0134] A high niobium stainless steel flux-cored welding wire, with a diameter of Φ=1.2, composed of iron sheet and flux-cored powder, the thickness of the iron sheet is 0.4 mm, the flux-cored powder is evenly filled and fills the cylindrical cavity formed by the iron sheet, the filling rate of the flux-cored powder is 28%, and the iron sheet is a 304L stainless steel strip;
[0135] The drug core powder, in terms of weight percentage, has the following components:
[0136] Niobium iron alloy powder 8%;
[0137] Rutile powder 30%;
[0138] Alumina powder 2%;
[0139] Iron oxide powder 1.5%;
[0140] Fluoride powder 3%;
[0141] Silicon dioxide powder 3%;
[0142] Titanium-iron alloy powder 1.5%
[0143] Zirconium iron alloy powder 1%
[0144] Bismuth oxide powder 0.35%
[0145] Manganese powder 4%;
[0146] Arc stabilizer 5%
[0147] Nickel powder 11%;
[0148] Chromium powder 19%;
[0149] Magnesium powder 1.5%;
[0150] Aluminum-iron alloy powder 1%;
[0151] Iron powder residue;
[0152] The fluoride powder is a mixture of cryolite and CeF3 in a mass ratio of 3:1.
[0153] The iron oxide powder is a mixture of ferric oxide and ferrous oxide in a mass ratio of 1:2.
[0154] A high niobium stainless steel flux-cored welding wire, the preparation method thereof has the following steps:
[0155] (1) Roll a 304L stainless steel strip into a U-shape, add a formulated amount of core powder into the U-shaped groove, and the average particle size of the core powder is 300 mesh;
[0156] (2) The U-shaped groove is rolled into an O-shaped steel tube, and the filling rate of the core powder in the O-shaped steel tube is 28%;
[0157] (3) The O-shaped steel pipe is rolled by 6 groups of 30 roller dies, drawn by 1 sizing die, and made into Φ2.0mm stainless steel flux-cored welding wire by wire annealing machine;
[0158] (4) The welding wire obtained in step (3) is further subjected to 10 drawing processes to be made into a Φ1.2 stainless steel flux-cored welding wire.
[0159] Example 5 is the same as Example 1, except that magnesium powder is not added in Example 5.
[0160] Example 6 is the same as Example 1, except that no aluminum-iron alloy powder is added in Example 6.
[0161] Comparative Example 1 is the same as Example 1, except that no rutile powder is added in Comparative Example 1.
[0162] Comparative Example 2 is the same as Example 1, except that no silicon dioxide powder is added in Comparative Example 1.
[0163] Comparative Example 3 is the same as Example 1, except that no silicon dioxide powder is added in Comparative Example 1, and the mass percentage of rutile powder is 22%.
[0164] Comparative Example 4 is the same as Example 1, except that no rutile powder is added in Comparative Example 1, and the mass percentage of silicon dioxide powder is 22%.
[0165] Comparative Example 5 is the same as Example 1, except that no fluoride powder is added in Comparative Example 5.
[0166] Comparative Example 6 is the same as Example 1, except that the fluoride powder in Comparative Example 6 is only CeF3.
[0167] Comparative Example 7 is the same as Example 1, except that the iron oxide powder in Comparative Example 7 is a mixture of ferric oxide and ferrous oxide in a mass ratio of 1:1.
[0168] Comparative Example 8 is the same as Example 1, except that the iron oxide powder in Comparative Example 8 is a mixture of ferric oxide and ferrous oxide in a mass ratio of 1:3.
[0169] Comparative Example 9 is the same as Example 1, except that the mass percentage of rutile powder in Comparative Example 9 is 11%, and the mass percentage of silicon dioxide powder is 11%.
[0170] Performance Testing
[0171] The flux-cored welding wires obtained in Examples 1-6 of the present invention and Comparative Examples 1-9 were used to perform cladding welding on stainless steel, and the obtained weld cladding metals were tested for relevant properties. Each group of parallel experiments was tested 10 times, and the average value was taken. The specific test results are shown in Table 1, Table 2, Table 3, and Table 4. After the flux-cored welding wires obtained in Examples 1-6 of the present invention and Comparative Examples 1-8 were cladding welded under pure CO2 protective gas, the compositions of the weld cladding metals obtained were shown in Table 4.
[0172] Weld deposited metal, tensile strength: the test standard is GB / T 228-2021.
[0173] Weld deposited metal, elongation at break: the test standard is GB / T 228-2121.
[0174] Weld deposited metal, impact energy: the test standard is GB / T 229-2020.
[0175] Bending performance: The test standard is GB / T 232-2010.
[0176] Intergranular corrosion: The test standard is method E in the Q1GB / T4334-2020 "Corrosion of Metals and Alloys - Test Method for Intergranular Corrosion of Austenite and Ferrite-Austenite (Duplex) Stainless Steel".
[0177] Table 1
[0178]
[0179] Table 2
[0180]
[0181] Table 3
[0182]
[0183] Table 4
[0184] ,
[0185] In Table 4, 8*C means 8 times the C content.
[0186] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A high niobium stainless steel flux-cored welding wire, characterized in that: After the cladding layer is welded, the weight percentage of niobium in the weld cladding metal is 0.8-1.2%, and the slag removal rate after all-position welding reaches more than 95%; The welding process is: using CO2 gas as the shielding gas, welding at 160A and 24V; Or use a mixed gas containing 85% Ar and 15% CO2 as the shielding gas and weld at 240A and 30V; Or a mixed gas containing 95% Ar and 5% CO2 is used as the shielding gas, and welding is performed at 200A and 28V; the high niobium stainless steel flux-cored welding wire comprises an iron sheet and flux-cored powder, the thickness of the iron sheet is 0.4mm, the flux-cored powder is uniformly filled and fills the cylindrical cavity formed by the iron sheet, the filling rate of the flux-cored powder is 22-28%, and the iron sheet is a 304L stainless steel strip; The drug core powder comprises the following components in terms of weight percentage: Niobium iron alloy powder 7-12%; Rutile powder 20-30%; Alumina powder 2-4%; Iron oxide powder 1-5%; Fluoride powder 3-4%; Silicon dioxide powder 2-3%; Titanium-iron alloy powder 1-3%; Zirconium-iron alloy powder 1-2%; Bismuth oxide powder 0.2-0.35%; Manganese powder 4-6%; Arc stabilizer 4-5%; Nickel powder 10-12%; Chromium powder 16-19%; Magnesium powder 0-1.5%; Aluminum-iron alloy powder 0-2% Iron powder residue; The weight ratio of the rutile powder to the silicon dioxide powder is 10:
1. The mass ratio of niobium to iron in the ferroniobium alloy powder is 7:3; The iron oxide powder includes at least one of ferric oxide and ferroferric oxide; The fluoride powder is a mixture of cryolite and lanthanide rare earth fluoride; The mass ratio of titanium to iron in the titanium-iron alloy powder is 3:7; The mass percentage of zirconium element in the zirconium-iron alloy powder is more than 98%; The arc stabilizer includes at least one of titanium oxide, magnesium oxide and potassium oxide; The mass ratio of aluminum element to iron element in the aluminum-iron alloy powder is 1:
1.
2. A high niobium stainless steel flux-cored welding wire according to claim 1, characterized in that: The fluoride powder is a mixture of cryolite and lanthanide rare earth fluoride in a mass ratio of 3:
1.
3. A high niobium stainless steel flux-cored welding wire according to claim 2, characterized in that: The lanthanide rare earth fluoride includes at least one of LaF3 and CeF3.
4. The high niobium stainless steel flux-cored welding wire according to claim 1, characterized in that: The iron oxide powder is a mixture of ferric oxide and ferrous oxide in a mass ratio of 1:
2.
5. The high niobium stainless steel flux-cored welding wire according to claim 1, characterized in that: The purity of manganese powder, nickel powder, chromium powder, iron powder and magnesium powder is greater than 99.9%.
6. The high niobium stainless steel flux-cored welding wire according to claim 1, characterized in that: The average particle size of the drug core powder is 300-500 mesh.
7. The high niobium stainless steel flux-cored welding wire according to claim 1, characterized in that: The added weight percentage of the magnesium powder is 1-1.5%.
8. The high niobium stainless steel flux-cored welding wire according to claim 1, characterized in that: The added weight percentage of the aluminum-iron alloy powder is 1-2%.
9. A high niobium stainless steel flux-cored welding wire according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: (1) Roll the 304L stainless steel strip into a U-shape and add the formulated amount of core powder into the U-shaped groove; (2) The U-shaped groove is rolled into an O-shaped steel pipe, and then rolled, bright annealed, drawn and reduced, and mechanically cleaned to obtain a Φ1.2-1.6mm high niobium stainless steel flux-cored welding wire.
Citation Information
Patent Citations
BE695021A
Novel calcium titanate slag system flux-cored wire and preparation method thereof
CN102717208A